G467(P) Audit of the quality of medical reports for children with special educational needs. (27th April 2015) - Goodson, A; Juniper, T; Lloyd, C; Miller, H; Reid, P; Rose, M
Abstract : Introduction: The purpose of the statutory assessment of a child's Special Educational Needs (SEN) is to gainclear picture of the whole child. Medical advice must be included and should describe any health provision reasonably required by the child's learning difficulties or disabilities. Families are now involved in the co-production of their child's Education Health and Care plan. For medical advice to be effective, it needs to be clear, accessible and specific, and ideally written in layman's terms. Aim: To assess the quality of the medical reports submitted to education for Statements of Special Educational Needs. Method: We audited all the medical reports submitted to education between January and June 2014 for a Statement of Special Educational Needs (SSEN). This work was part of pilot exploring data collection on child disability for planning purposes. A limited number of quality indicators were selected from medical advice guidelines. Data on coexisting health needs and actions arising were also recorded. Results: A total of 125 reports were analysed for children, median age 8.8 years, 74% boys. 48% of the reports were derived from existing medical records. 52% of reports were generated after a new medical consultation. Results from this latter group are presented. 85% reports recorded growth, 85% vision, 72% hearing and 65% all three. Many medicals made reference to a lack of background information, especially for children with SEMH, ASD/ADHD. Advice related to the child's SEN and to associated medical problems (such as asthma) was not written consistently. Many associated health problems were identified: 11% of children were overweight, 18% obese. 17% had visual problems, 14% nutritional, 15% continence, 11% general medical problems. In many instances these problems were severe enough to prompt referral to therapy services for 9%, to CAMHS 8%, continence 5%, general medical 9%. Conclusions: The quality and detail of the medical reports was very variable and the medical examination identified many unmet health needs that might otherwise not have been recognised. These findings will be used to inform the crafting of medical advice and the development of new tools and guidelines for EHC plans.